Generalized hooke law for relativistic membranes and p-branes - Zheltukhin, A.A. (Вопросы атомной науки и техники, 2012)
The character of elastic forces of relativistic membranes and p-branes encoded in their nonlinear equations is studied. The toroidal brane equations are reduced to the classical equations of anharmonic elastic media described by monomial potentials. Integrability of the equations is discussed and some of their exact solutions are constructed. Исследуется характер сил упругости, задаваемых нелинейными уравнениями релятивистских мембран и р-бран. Уравнения тороидальных бран преобразуются к классическим уравнениям ангармонических упругих сред, описываемых мономиальными потенциалами. Обсуждается интегрируемость полученных уравнений и находятся некоторые их частные решения. Досліджується характер сил пружності, які задані нелінійними рівняннями релятивістських мембран та р-бран. Рівняння тороідальних бран перетворюються у класичні рівняння ангармонічних пружних середовищ, що описуються мономіальними потенціалами. Обговорюється інтегрування отриманих рівнянь. Знайдені їх деякі часткові рішення.